Vessel strike encounter risk model informs mortality risk for endangered North Atlantic right whales along the United States east coast - Hannah Blondin; Lance P. Garrison; Jeffrey D. Adams; Jason J. Roberts; Caroline P. Good; Meghan P. Gahm; Niki E. Lisi; Eric M. Patterson (Scientific Reports)
Abstract Vessel strikes are a critical threat to endangered North Atlantic right whales (Eubalaena glacialis), significantly contributing to their elevated mortality. Accurate estimates of these mortality rates are essential for developing effective management strategies to aid in the species’ recovery. This study enhances existing vessel strike models by incorporating detailed regional data on vessel traffic characteristics as well as whale distribution and behavior. Our model assesses the spatial and temporal variability in vessel strike risk along the U.S. east coast apportioned into three vessel length classes (26–65 feet, 65–350 feet, > 350 feet). By including regional right whale depth distributions and parameterizing potential whale avoidance based on factors such as descent rate, bottom depth, and vessel speed and size, the model provides a refined estimation of mortality risk. We also address the underrepresentation of smaller vessel activity via a correction factor, offering a more accurate annual mortality risk estimate for each vessel size class. These findings highlight that vessels > 350 feet in length pose the greatest risk to right whales. Simulations of reduced vessel speeds indicate that speed measures can mitigate mortality rates; however, residual risk remains even at speeds of 10 knots or less suggesting limitations to this mitigation approach.